The Political Economy of Corruption and the Role of Financial Institutions - Kira Börner; Christa Hainz (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2004)
In transition and developing countries, we observe rather high levels of corruption even if they have democratic political systems. This is surprising from a political economy perspective, as the majority of people generally suffers from high corruption levels. Our model is based on the fact that corrupt officials have to pay an entry fee to get lucrative positions. In a probabilistic voting model, we show that a lack of financial institutions can lead to more corruption as more voters become part of the corrupt system. Well-functioning financial institutions, in turn, can increase the political support for anti-corruption measures.
urn:nbn:de:bvb:19-epub-411-6
Keywords: D73; D72; O17; 330; Corruption; Financial Markets; Institutions; Development; Voting